INTRODUCING ENGLISH VOCABULARIES TO CHILDREN BY JOLI-JOLI PLAY - Elise Muryanti; Yuli Herman (ELP (Journal of English Language Pedagogy), 2019)
This study aims to determine to what extent the effectiveness of the method of Joli -Joli play to children English vocabulary mastery in a kindergarten Padang, West Sumatera Indonesia. This study used a quasi experiment. The data was collected through Total sampling techniques. The Data collection techniques used tests. Then the data is processed with difference test (t-test). The result shows that the children in the experimental class using Joli-Joli Game the mean is higher when compared to children in control class using Pak Police game. Based on the calculation of the t-test obtained t calculated greater than t_table, it indicates that there is a significant difference between these two classes. It can be concluded that the use of Joli Joli play method contributes a significant influence on the mastery of children English vocabulary.